Female and low‐ and middle‐income authorship trends in high‐impact ENT journals (2011–2020). Issue 2 (20th March 2023) - Jashek‐Ahmed, Farizeh; Daudu, Davina; Heer, Baveena; Ali, Hawa; Wiedermann, Joshua; Seguya, Amina; ,
Abstract: Introduction: Despite a recent drive to increase diversity, the global academic workforce is skewed in favor of authors from high‐income countries, and women are under‐represented in the published medical literature. Objectives: To explore the trends in authorship of three high‐impact otolaryngology journals over a ten‐year period (2011–2020). Methods: Journals selected: JAMA Otolaryngology–Head and Neck Surgery, The Laryngoscope and Rhinology. Articles were reviewed from four issues per journal per year, and data was collected on: time of publication; subspeciality; number of authors; sex of first and last authors; country of practice of first author and country where each study was conducted. Trends were examined though univariate and multivariate logistic regression models. Results: 2998 articles were included. 93.9% of first authors and 94.2% of studies were from high‐income countries. Women were first authors in 31.5% ( n  = 912) and senior authors in 18.4% ( n  = 524) of articles. Female first authorship significantly increased between 2011 and 2020 however female senior authorship remained the same. There have been no significant changes in the proportion of published articles from low‐and middle‐income countries (LMIC) over time ( p  = .65). Amongst the LMIC articles, 72% came from Brazil, Turkey or China and there were no published papers from countries with a low‐income economy (gross national income per capita of $1085 or less). Conclusions: Although female first authorship has increased in the last decade, there has been minimal other demographic change in authorship over this time. High‐impact otolaryngology journals poorly represent academia in low‐and‐middle income countries. There is a need for increased advocacy promoting gender and geographical research equity in academic medicine. Level of Evidence: III. Abstract : This study included 2998 articles from three high‐impact journals between 2011 and 2020 There has been no significant increase in the proportion of authors from low‐and ‐middle income countries (6.1%) during this time.Whilst the proportion of female first authors has significantly increased between 2011 and 2020 (OR 2.0, 95% CI 1.4–2.8) no change was observed in female senior authorship over time (18.4%).